Relevance of obesity as an etiology of secondary hypogonadism: an integrative review (Research, Society and Development, 2022)
This article aims to assess the impact of obesity as a cause of secondary hypogonadism. This is an integrative literature review, which included studies published between 2017 and 2022, through Pubmed, LILACS and Cochrane databases. The descriptors were used: “Hypogonadism”, “Infertility” and “Obesity”. After applying the inclusion and exclusion criteria, 14 studies were selected to compose this review. This research responded to the established objectives, highlighting the importance of obesity as an etiology of hypogonadism, through the analysis of data regarding the frequency of these two alterations and the pathophysiological mechanisms of obesity in the reproductive system, in order to define bases for the diagnosis and detection of complications. It is noticed that obesity alters gonadal function from hormonal changes, generation of a chronic inflammatory state, damage to genetic material, disturbance of the immune system, among others. The diagnosis of hypogonadotropic hypogonadism, typical of obesity, is based on the finding of low serum gonadotropin levels with inappropriately low/normal concentrations of luteinizing hormone (LH) and follicle stimulating hormone (FSH). In women, the main complications are related to Polycystic Ovary Syndrome (PCOS). These alterations are associated with Infertility, Diabetes Mellitus and cardiovascular alterations.